Moderating role of financial performance on the relationship between board attributes and corporate sustainability disclosure compliance - Bello, Mohammed Sabo; Mohd Said, Ridzwana; Johari, Jalila; Kamarudin, Fakarudin (Universiti Putra Malaysia, 2022)
The concept of financial performance is of great concern to stakeholders. This empirical paper investigates the moderating role of financial performance on the link between board attributes and corporate sustainability disclosure compliance (CSDC). The going concern of a company depends on its ability to generate returns from operating, investing, and financing activities. Thus, it is crucially important to explore the extent to which a firm's financial performance strengthens the influence of firm-level determinants of CSDC. The sample for the current study consists of 118 Nigerian-listed companies over seven years between 2011 and 2017. The dynamic GMM regression analysis is used for data analysis. The GMM results reveal the moderating effect of return on assets and return on equity on the influence of firm and board attributes on CSDC, evident from significant positive interaction with board size, board independence, gender diversity and audit committee. This implies that when firms gain financial strength to engage in more sustainable activities, this increases the level of corporate sustainability disclosure compliance.